Sovereignty and Political Representation. Issue 1 (1st April 2014) - Ankersmit, Frank
Abstract : Modern Time – the period from 1500 to 1800 – began by adding to political thought the notion of sovereignty and ended by enriching it with what is nowadays understood as political representation. These two notions have traditionally been seen as the two pillars supporting both modern democracy and our conviction that popular sovereignty is what makes our contemporary democracies into the best political system ever conceived. However, the big problem is that sovereignty and political representation are hard to reconcile with each other: the relationship between the two of them is much like that between the two partners in a marriage permanently on the verge of divorce. This essay tries to explain why this is so and why Rousseau was basically right when intimating as much already in his Du Contrat Social . It does so by considering the relevant aspects in the history of political thought from the Middle Ages down to the so-called doctrinaire liberals of the beginning of the 19 th century. Doing so compels us to recognize a basic inconsistency at the very heart of our modern democracies and its nasty consequences for the position of the people's representatives.